HUBUNGAN FAKTOR PEMBENTUK SIKAP DENGAN SIKAP PETANI PADA PROGRAM PENINGKATAN PENDAPATAN PETANI KECIL (P4K) DI KECAMATAN TOROH KABUPATEN GROBOGAN - SUMINAH, SUMINAH (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2008)
Most farmers are poor farmers characterized with low capital and income degrees. Poor farmer income improvement program (P4K) was an effort increasing or improving farmer incomes through group efforts, by giving them capital loans to develop or start a bussiness.